The road headed west : a 6,000-mile cycling odyssey through North America - McCarron, Leon (Skyhorse Publishing, 2014)
"What happens when you swap the nine-to-five for two wheels and a journey of a lifetime? Terrified of the prospect of a life spent behind a desk, without challenge or excitement, Leon takes off to cross America on an overloaded bicycle packed with everything but common sense. Over five months and 6000 miles, he cycled from New York to Seattle and then on to the Mexican border, facing tornados, swollen river crossings, wild roaming buffalo and one hungry black bear along the way. But he also met kind strangers, who offered their food, wisdom, hospitality and even the occasional local history lesson, and learned what happens when you take a chance and follow the scent of adventure. With a sharp eye and a genuine go-where-the-wind-takes-me attitude, McCarron makes for an ideal guide on this cycling adventure. He passes through small towns, rolls up and flies down the winding roads of the Blacks Hills is taken in and fed by strangers, all on a quest to discover the 'real' America, and in the process, learn a little about himself. Funny, insightful, and full of life, The Road Headed West will inspire readers to chase their dreams and go off in search of adventure"--